Profiling protein expression in circulating tumour cells using microfluidic western blotting - Sinkala, Elly (Nat Commun, 2017)
Circulating tumour cells (CTCs) are rare tumour cells found in the circulatory system of certain cancer patients. The clinical and functional significance of CTCs is still under investigation. Protein profiling of CTCs would complement the recent advances in enumeration, transcriptomic and genomic characterization of these rare cells and help define their characteristics. Here we describe a microfluidic western blot for an eight-plex protein panel for individual CTCs derived from estrogen receptor-positive (ER+) breast cancer patients. The precision handling and analysis reveals a capacity to assay sparingly available patient-derived CTCs, a biophysical CTC phenotype more lysis-resistant than breast cancer cell lines, a capacity to report protein expression on a per CTC basis and two statistically distinct GAPDH subpopulations within the patient-derived CTCs. Targeted single-CTC proteomics with the capacity for archivable, multiplexed protein analysis offers a unique, complementary taxonomy for understanding CTC biology and ascertaining clinical impact.